2013
DOI: 10.1371/journal.pone.0058861
|View full text |Cite
|
Sign up to set email alerts
|

Does Exercise Improve Glycaemic Control in Type 1 Diabetes? A Systematic Review and Meta-Analysis

Abstract: ObjectiveWhilst regular exercise is advocated for people with type 1 diabetes, the benefits of this therapy are poorly delineated. Our objective was to review the evidence for a glycaemic benefit of exercise in type 1 diabetes.Research Design and MethodsElectronic database searches were carried out in MEDLINE, Embase, Cochrane’s Controlled Trials Register and SPORTDiscus. In addition, we searched for as yet unpublished but completed trials. Glycaemic benefit was defined as an improvement in glycosylated haemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
129
1
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(153 citation statements)
references
References 27 publications
10
129
1
13
Order By: Relevance
“…Our study detected improvements in mean HDL of 4.7% (8-30% in published studies), triglyceride of 10% (13-15% in published studies) and insulin resistance of 20% (up to 23% in published studies). In line with other studies, there was no improvement in glycaemic control with exercise [29].…”
Section: Discussionsupporting
confidence: 91%
“…Our study detected improvements in mean HDL of 4.7% (8-30% in published studies), triglyceride of 10% (13-15% in published studies) and insulin resistance of 20% (up to 23% in published studies). In line with other studies, there was no improvement in glycaemic control with exercise [29].…”
Section: Discussionsupporting
confidence: 91%
“…Yardley et al (2014) found a significant reduction in post-treatment HbA1c in four out of six studies but there was also one trial which showed no decrease at all [8]. Another even larger meta-analysis could not find evidence for a glycaemic benefit of exercise when followed by HbA1c [7], thus the issue remains unsolved.…”
Section: Discussionmentioning
confidence: 99%
“…Current literature is inconsistent whether exercise has a meaningful effect on HbA1c [6][7][8]. Beraki et al (2014) reported lower HbA1c levels in active persons with diabetes than in sedentary ones in a large cohort [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of research investigating the impact of exercise in persons with type 1 diabetes is limited to exercise durations for up to 2 hours per session [22,23]. As such, most information on glycemic control during and after prolonged physical activity (>2 h) can be considered as 'anecdotal evidence'.…”
Section: Discussionmentioning
confidence: 99%